An introduction to car loan interest charges / Ch’ng Pei Eng ... [et al.] - Ch’ng, Pei Eng; Ng Set, Foong; Chew, Yee Ming; Hamat, Muniroh (Unit Penerbitan JSKM, 2020)
Many people love cars, but the price of a car is usually not cheap, so asking a bank loan is the easiest way to solve this financial problem. Do you know that money is not free to borrow? There is a cost to pay when one borrow money! Interest is the name for the cost of borrowing money. In this paper, we would like to share how the interest is being calculate for a car loan, how to determine the monthly payment for a car loan, as well as the total amount paid over a period of car loan term for the car. This would help the reader to make a smart decision when taking a car loan in future.